2017
DOI: 10.1016/j.jcrs.2017.03.034
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcomes after multifocal intraocular lens exchange

Abstract: Multifocal IOL exchange can be performed safely with good visual outcomes using different types of IOLs. A lower refractive prediction error and a higher likelihood of 20/40 or better vision can be achieved with the implantation of the second IOL compared with the original multifocal IOL, regardless of the final IOL position.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 26 publications
0
21
0
4
Order By: Relevance
“…TCT, IOP and diopter are presumed to be associated, although this is debated. The corneal thickness is reduced in myopia ( 28 ) and it has been determined that for each 70-µm decrease, the IOP as measured with a tonometer is 3.5 mmHg lower than the baseline value ( 29 ); however, other studies have not indicated any correlation between diopter and IOP ( 30 ). By contrast, a larger diopter was suggested to be associated with higher IOP ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…TCT, IOP and diopter are presumed to be associated, although this is debated. The corneal thickness is reduced in myopia ( 28 ) and it has been determined that for each 70-µm decrease, the IOP as measured with a tonometer is 3.5 mmHg lower than the baseline value ( 29 ); however, other studies have not indicated any correlation between diopter and IOP ( 30 ). By contrast, a larger diopter was suggested to be associated with higher IOP ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…При имплантации современных моделей эластичных ИОЛ в значительной части случаев возможна имплантация второй линзы в перпендикулярный меридиан капсульного мешка. В случаях отсутствия капсульного кармана из-за слипания задней капсулы с краем капсулорексиса вторая линза имплантируется в цилиарную борозду [23,49,50]. В случае дискомфорта из-за полученной миопии показано выполнение эксимерлазерного вмешательства на роговице, но при наличии противопоказаний к его проведению возможна реимплантация ИОЛ соответствующей оптической силы [50,51].…”
Section: обзоры литературы Literature Reviewsunclassified
“…В случаях отсутствия капсульного кармана из-за слипания задней капсулы с краем капсулорексиса вторая линза имплантируется в цилиарную борозду [23,49,50]. В случае дискомфорта из-за полученной миопии показано выполнение эксимерлазерного вмешательства на роговице, но при наличии противопоказаний к его проведению возможна реимплантация ИОЛ соответствующей оптической силы [50,51]. У больных с короткой переднезадней осью глазного яблока, в особенности с микрофтальмом, чаще всего производят имплантацию двух ИОЛ -piggyback ИОЛ.…”
Section: обзоры литературы Literature Reviewsunclassified
See 1 more Smart Citation
“…Die durchschnittliche Zeit bis zur Explantation betrug 7,9 ± 9,2 Monate (Bereich: 3 Tage -40,5 Monate). Kim et al [9] Das Herausfinden, welcher Patient für Multifokallinsen geeignet ist und welcher nicht, bleibt nach wie vor eine Herausforderung. Insbesondere bei Prelex-Operationen sollte die präoperative Aufklärung so umfassend wie nur möglich durchgeführt und dokumentiert werden.…”
Section: Diskussionunclassified